Effects of cryogenic temperature and grain size on fatigue-crack propagation in the medium-entropy CrCoNi alloy. (November 2020) - Rackwitz, Julian; Yu, Qin; Yang, Yang; Laplanche, Guillaume; George, Easo P.; Minor, Andrew M.; Ritchie, Robert O.
Abstract: CrCoNi-based high-entropy alloys have demonstrated outstanding mechanical properties, particularly at cryogenic temperatures. Here we investigate the fatigue-crack propagation properties of the equiatomic, single-phase, face-centered cubic, medium-entropy alloy (MEA), CrCoNi, that displays exceptional strength, ductility and toughness, all of which are enhanced at cryogenic temperatures. Fatigue-crack growth is examined, at a load ratio of 0.1 over a wide range of growth rates, from 10 −11 to >10 −7 m/cycle, at room (293 K) and cryogenic (198 K, 77 K) temperatures for two grain sizes ( 7 and 68 µm), with emphasis on near-threshold behavior. We find that the Δ K th fatigue thresholds are increased with decreasing temperature and increasing grain size: from 5.7 MPa√m at 293 K to 8 MPa√m at 77 K in the fine-grained alloy, and from 9.4 MPa√m at 293 K to 13.7 MPa√m at 77 K in the coarse-grained alloy. Mechanistically, transgranular cracking at 293 K transitions to a mixture of intergranular and transgranular at cryogenic temperatures, where the increased propensity of nano-twins appears to inhibit growth rates by deflecting the crack path. However, the main factor affecting near-threshold behavior is roughness-induced crack closure from interference between the crack flanks, which is enhanced by the rougher fracture surfaces at low temperatures, particularly in the coarser-grained microstructure. Fatigue-crack propagation behavior in CrCoNi is comparable to nickel-based superalloys but is superior to that of the high-entropy CrMnFeCoNi (Cantor) alloy and many high-strength steels, making the CrCoNi alloy an excellent candidate material for safety-critical applications, particularly involving low temperatures. Graphical abstract: Image, graphical abstract